Early life antibiotic exposure and inflammatory bowel disease: Role of antibiotics in inflammatory bowel disease - Agrawal, Rashmi; Agrawal, Amit; Jacson, Janice (Indian Journal of Child Health, 2024)
Inflammatory bowel disease (IBD) is known to affect millions of people worldwide and is primarily caused due to abnormal due to abnormal immune responses to intestinal microbes. IBD is primarily categorized under two main types – ulcerative colitis and Crohn’s disease. Although the cause of IBD is still an unsolved puzzle, its development can be attributed to the presence of various risk factors including antibiotic use. The intestinal immune system is the point of genesis of IBD and anything that creates an imbalance can trigger IBD. Alterations in the gut microbiota can lead to reduced microbial populations and lead a chronic inflammation state. Antibiotics may influence microbial maturity and can hamper the formation of a strong immune system. This makes an individual vulnerable to the threat of infections and subsequent development of a chronic inflammation state. Studies have implicated that the use of antibiotics during pregnancy, antepartum, and among neonates is associated with the development of IBD. Adequate development of the microbial niche takes place within the first 2 years of life and extensive administration of antibiotics during this period can pose a significant risk for the development of IBD. Animal studies have also documented the role of in utero antibiotic exposure during the antepartum period and the subsequent risk of developing IBD in the offspring. This review summarizes the role of antibiotic exposure during pregnancy and infancy in the development of IBD.